Explaining Agriculture Faculty Members’ Involvement in Study Abroad: Structural Relationships Among Personal - Dimension Variables - Shelli D. Rampold; Melissa Cater; J C. Bunch; J. Joey Blackburn; Michael Burnett (Journal of International Agricultural and Extension Education, 2018)
Agriculture faculty members’ involvement in study abroad programs can influence students’ participation in such. However, faculty members’ involvement may be limited by institutional, professional, and personal factors. This study was conducted to explain agriculture teaching faculty members’ involvement in study abroad programs by examining the structural relationships between their study abroad involvement and personal dimension variables. Results indicated the personal factors influencing faculty members’ involvement in study abroad include their perceptions of the knowledge, skill, and ability (KSA) outcomes of study abroad, awareness of study abroad programs and procedures, and prior international experience (PIE). The effect of faculty members’ perceptions of the KSA outcomes of study abroad programs on their involvement was mediated by their perceptions of the importance of those KSA outcomes for professionals in their field. Further, faculty members’ perceived importance of KSA outcomes was moderated by PIE. Recommendations for future practice include providing professional development and training to increase faculty members’ awareness of study abroad and increase opportunities for faculty members to gain international experiences. Future research should include replication of this study with agriculture faculty members at other institutions and the examination of relationships among professional and institutional dimension factors
Keywords: agriculture faculty; faculty involvement; personal factors; study abroad